Development and heat treatment of functionally graded 316L stainless steel-tungsten carbide coatings manufactured using laser cladding - Tendere, Takudzwa Lewis (Stellenbosch : Stellenbosch University, 2024)
Thesis (MEng)--Stellenbosch University, 2024.